Sensory Evaluation, Nutritional Composition, and Antioxidant Activity of Fresh Milk Fortified with Mistletoe Leaf (Dendrophthoe Pentandra) Extract - Dwi Denintia; Ai Kustiani; Adhi Nurhartanto (CV. CENDIKIA JENIUS INDONESIA, 2025)
Fresh milk is a highly nutritious beverage but has relatively low antioxidant activity, thus requiring development into a functional food. Fortification with mistletoe leaf extract (Dendrophthoe pentandra), which contains bioactive compounds such as flavonoids, phenols, and tannins, has the potential to enhance the functional value of milk. This study aimed to evaluate the sensory characteristics, nutritional composition, and antioxidant activity of fresh milk fortified with mistletoe leaf extract. This experimental research used a Completely Randomized Design (CRD) with five treatments (F0–F4), namely 0, 2, 4, 6, and 8 grams of extract per 100 mL of milk. Data were collected through a hedonic test involving 15–25 semi-trained panelists, proximate analysis (water, protein, fat, carbohydrates, ash), and antioxidant activity measurement using the DPPH method. The research was conducted from May to June 2025 at Mitra Indonesia University and the Laboratory of POLINELA. The results showed that fortification affected sensory attributes (especially taste and color) but maintained the nutritional quality according to the Indonesian National Standard (SNI 3141.1:2011). Antioxidant activity increased with higher extract concentrations, with the F2 formulation (4 grams) offering the best balance between sensory quality and antioxidant content. In conclusion, fortification of fresh milk with mistletoe leaf extract effectively improves its functional properties without compromising nutritional value. It is recommended that the F2 formulation be considered for further development of functional milk products based on natural ingredients.